2007
DOI: 10.2169/internalmedicine.46.0271
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Sonography of the Substantia Nigra in Japanese Patients with Parkinson's Disease or Atypical Parkinsonism: Clinical Potential and Limitations

Abstract: Objective There is growing interest in the use of transcranial sonography (TCS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 17 publications
(14 reference statements)
5
55
2
Order By: Relevance
“…Previous efforts have reported a 10%-20% rate of inadequate acoustic bone windows, especially in women and the elderly, in up to 59% of Asian old women 10 , and, perhaps, in patients with osteoporosis 1,8 . Although conclusions can only be drawn with caution, as the number of participants was rather small in this pilot study, only 10.8% of our participants lacked adequate bone windows.…”
Section: Discussionmentioning
confidence: 99%
“…Previous efforts have reported a 10%-20% rate of inadequate acoustic bone windows, especially in women and the elderly, in up to 59% of Asian old women 10 , and, perhaps, in patients with osteoporosis 1,8 . Although conclusions can only be drawn with caution, as the number of participants was rather small in this pilot study, only 10.8% of our participants lacked adequate bone windows.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies demonstrated good sensitivity and specificity of TCS for the differentiation of PD and aPS. In independent studies, it could be shown that SN hyperechogenicity is only rarely found in MSA-P and in not more than one third of PSP patients [25][26][27][28] . In addition to SN echogenicity, also LN echogenicity and the width of the third ventricle ( fig.…”
Section: Tcs In the Differential Diagnosis Of Pdmentioning
confidence: 99%
“…In particular at later stages -but also in the onset early in the course of the disease [13] -TCS was reported to discriminate IPD from MSA-P and PSP [2,57], with a high sensitivity and specificity [23,26,61]. This was applied and calculated using the frequency and the distribution of TCS abnormalities of the substantia nigra, lenticular nucleus and third ventricle (Figure 2 A-B) ( Figure 3) [23,25,26].…”
Section: Tcs In Apsmentioning
confidence: 99%
“…This was applied and calculated using the frequency and the distribution of TCS abnormalities of the substantia nigra, lenticular nucleus and third ventricle (Figure 2 A-B) ( Figure 3) [23,25,26]. More specifically a pooled analysis of several studies [13,23,25,29,61] including 500 patients with adequate assessability on TCS, of whom 353 had definite PD, 86 had probable or possible MSA-P, and 61 had probable or possible PSP, has shown that hyperechogenicity of the SN and normal echogenicity of the basal ganglia has a positive predictive value of 91% for IPD [24]; normal echogenic SN combined with LN hyperechogenicity indicated MSA-P or PSP (sensitivity59%-specificity100%; positive predictive value 100%); normal echogenic SN indicated MSA-P rather than IPD (sensitivity 90%-specificity 98%; positive predictive value 86%); third-ventricle dilatation of more than 10 mm in combination with LN hyperechogenicity indicated PSP rather than IPD (sensitivity 84%-specificity 98%; positive predictive value 89%). In parkinsonism with an age at onset younger than 60 years, normal echogenic SN alone indicated MSA or PSP (sensitivity 75%-specificity 100%; positive predictive value 100%) [23].…”
Section: Tcs In Apsmentioning
confidence: 99%
See 1 more Smart Citation